Childbirth Experience among Primi Postnatal Mothers in a Teaching Hospital - Banjara, Laxmi; Shrestha, Niran (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Childbirth is a crucial event in a woman’s life. Women-centered care for positive childbirth experiences is currently a global trend. The aim of the study is to assess childbirth experience among primi postnatal mothers. Methods: The cross-sectional analytical study was carried out at postnatal ward of Patan Hospital among 122 primi postnatal mothers. Structured likert scale questionnaires were used for data collection. Data analysis was done and frequency, mean and standard deviation were calculated for socio-demographic, obstetric characteristics along with level of childbirth experience. Chi square test was done to measure association between sociodemographic characteristics and obstetric characteristics with childbirth experience. Results: Among 122 mothers, most (84.4%) had positive childbirth experience and 15.6% had negative childbirth experience. Significant association was found between age (P = 0.00), education (P = 0.00) and duration of labor (P = 0.00) with childbirth experience. Conclusions: This study revealed that most of the mothers had positive childbirth experience and it is associated with age, education and labor duration.